The glucosylceramide synthase inhibitor PDMP causes lysosomal lipid accumulation and mTOR inactivation - Hempelmann, Pia; Höglinger, Doris (International journal of molecular sciences, 2021)
For many years, the biology of glycosphingolipids was elucidated with the help of glucosylceramide synthase (GCS) inhibitors such as 1-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP). Additionally, PDMP gained interest because of its chemosensitizing effects. Several studies have successfully combined PDMP and anti-cancer drugs in the context of cancer therapy. However, the mechanism of action of PDMP is not fully understood and seems to go beyond glycolipid inhibition. Here, we used a functionalized sphingosine analogue (pacSph) to investigate the acute effects of PDMP on cellular sphingolipid distribution and found that PDMP, but not other GCS inhibitors, such as ND-DNJ (also called Miglustat), induced sphingolipid accumulation in lysosomes. This effect could be connected to defective export from lysosome, as monitored by the prolonged lysosomal staining of sphingolipids as well as by a delay in the metabolic conversion of the pacSph precursor. Additionally, other lipids such as lysobisphosphatidic acid (LBPA) and cholesterol were enriched in lysosomes upon PDMP treatment in a time-dependent manner. We could further correlate early LBPA enrichment with dissociation of the mechanistic target of rapamycin (mTOR) from lysosomes followed by nuclear translocation of its downtream target, transcription factor EB (TFEB). Altogether, we report here a timeline of lysosomal lipid accumulation events and mTOR inactivation arising from PDMP treatment.